Pattern of obesity among chief executives of public and private organizations in Jos, Plateau state, Nigeria - Banwat, Mathilda; Chingle, Moses; Lar, Luret; Dami, Nantok; Zoakah, Ayuba (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background: Obesity and overweight are known to be associated with other non-communicable diseases (NCD). In recent times, there has been an increase in the prevalence of this healthrelated condition, not only in the developed but also in developing countries. This study set out to assess the prevalence and factors associated with this health condition among chief executives of private and public organizations in Jos metropolis.Materials and Methods: A total of 250 chief executives of public and private institutions in Jos north local government area (LGA) of Plateau State were selected using a multi-stage sampling technique and data was collected from them using interviewer-administered, structured questionnaires. The data were analyzed using Epi Info statistical software (version 3.5.3).Results: The ages of the respondents ranged between 27 and 68 years with a mean of 44 + 2 years. Majority of the respondents (68%) were males. The prevalence of obesity was found to be 38% while 48.8% of subjects were overweight. BMI of subjects had a statistically significant relationship with sex and income of respondents but not with exercise. There was a fair knowledge of obesity, its contributory factors, and complications among the respondents (63.6%). Conclusion: The prevalence of obesity and overweight were found to be high among the studied executives, despite their fair knowledge of the disease and its complications. The increasing prevalence of obesity among chief executives of organizations needs to be addressed by increased health education. Managements of organizations should insist on periodic medical check-ups for their executives.
Keywords: Chief executives; obesity; overweight; prevalence